Fatal Sarcoptes scabiei and Demodex sp. co-infestation in wolves (Canis lupus) at the Białowieża National Park, Poland – is it a consequence of climate change? - Krzysiak Michał K.; Świątalska Agnieszka; Plis-Kuprianowicz Elwira; Konieczny Andrzej; Bakier Sławomir; Tomczuk Krzysztof; Larska Magdalena (Journal of Veterinary Research)
In winter 2021/2022, a wolf population in the primeval Białowieża Forest in Poland was struck by an outbreak of severe mange caused by mixed infestations of Sarcoptes and Demodex mites. We present an epidemiological analysis of this mange which caused significant morbidity and mortality.